CFD analysis for counter flow in concentric tube heat exchangers - Mohan, Banoth; Ashok Kumar, V (International Journal of Engineering and Technology, 2018)
A device may be a device worked for the sensible heat exchange beginning with one liquid then onto the attendant, paying very little reference to whether or not the liquids square measure isolates by a powerful divider in order that they ne’er mix, or the liquids square measure particularly in touch. reliably get some data concerning in device progression is creating to form productive, traditionalist and stinting heat exchangers, where for the duration of the planet. Strengthening the function for this alteration wants associate degree association. In most up-to-date 5 years coaxial tube heat exchangers use unnatural convection to cut down the temperature of a operating liquid whereas raising the temperature of the cooling medium. The motivation driving this paper is to utilize ANSYS FLUENT12.1 programming and hand counts to interrupt down the temperature drops as a neighborhood of each straight speed and delta temperature and the way each modification with the opposite. every gleam money dealer show was worked in steps and examined in transit till the purpose that the instant that each parallel stream and counter stream heat money dealer models were created. The outcomes were thought of between every model and among parallel and counter stream with fouled funneling. Turbulent stream was conjointly impecunious down amidst the distinction within the shine exchangers to choose its impact on heat exchange. whereas clearly the fouled heat money dealer had a lower execution and during this manner cooled the operating liquid less, the execution of the counter heat money dealer out of the blue of the parallel heat money dealer.